Efektifitas Instalasi Pengolahan Air Limbah Rumah Sakit “X” Kabupaten Banjar - Arifin Arifin; Istiqamah Istiqamah; Sulaiman Hamzani (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2016)
Abstract: Effectivity of waste water treatment installations in Hospital’s X Banjar Regency.Hospital’s X has a wastewater treatment Installations which began operating from the year 2008 – until now. The system uses the wastewater treatment Installations processing system for aerobic and anaerobic biological in a wastewater treatment process using media hive of bees to do the filtering. In the media there is a biofilm that attached to the media hive of bees to help the process of decomposition of organic and inorganic materials. This research aims to know the performance of waste water treatment installations in Hospital’s X  Banjar Regency. This type of research is descriptive, i.e. describe the performance measurement quality by doing the wastewater treatment Installations for parameters pH, temperature, BOD, COD, TSS, and free Ammonia (NH3-N) and compared with Regulation of South Kalimantan Governor number 04 in 2007 about the raw quality of liquid waste for the activities of the hospital. The research design used observation, interviews and measurements. Method of sampling used composite sampling. The results showed that the performance of the the wastewater treatment Installations at Hospital’s X still hasn't been fullest measurement results from the laboratory, the value of the measurement of BOD, COD, TSS and Ammonia free still not qualify. This is due to the existence of problems on aerobic processing, bak bak bak pengendap end, chlorination and a monitoring that is the abundance of mud that settles in the base of the tub because it never done drain the mud. Efforts to improve the performance of the the wastewater treatment Installations i.e. preferably done drain sludge routinely on the bak-bak processing every 6 months, installing blower manual in aerobic processing and adds additional equalization tubs. Keywords: Effectivity of the wastewater treatment Installations, waste water, hospital